HELMINTOFAUNA OF THE FELIS CHAUS NEMATODA CLASS IN THE CONDITIONS OF KARAKALPAKSTAN - Kongratbaeva, Paruaz Oserbaevna (SCIENCE and SOCIETY, 2026)
14 species of helminths belonging to the class of nematodes were recorded in the reed cat. They belong to 1 type, 1 class, 6 orders, 10 families, and 11 genera. As a result of the research, 19 field cats were infected with 14 species of helminths belonging to the class of nematodes.